1976
DOI: 10.1149/1.2132656
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Cobalt Using an Insoluble Anode

Abstract: A method has been developed which permits the use of an insoluble anode to electrodeposit cobalt by the addition of a sufficient amount of an electrochemically active substance such as vanadium pentoxide to the cobalt sulfate plating solution. In the absence of such additions, formation of Co3+ ions and cobalt oxide false(Co2O3false) at the platinum anode results during plating. The effects of the addition of vanadium pentoxide on the electrode process during plating have been investigated through the analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
2

Year Published

1977
1977
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 4 publications
0
5
0
2
Order By: Relevance
“…The preparation of lead alloys (for example, in Pb–Co systems) is accompanied by some challenges, one of which is the immiscibility of most of the elements in lead [ 7 ]. Cobalt has been added to lead anodes as an alloy element since 1917 [ 8 ]. The addition of cobalt to lead anodes is accompanied by an electro-catalytic improvement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of lead alloys (for example, in Pb–Co systems) is accompanied by some challenges, one of which is the immiscibility of most of the elements in lead [ 7 ]. Cobalt has been added to lead anodes as an alloy element since 1917 [ 8 ]. The addition of cobalt to lead anodes is accompanied by an electro-catalytic improvement.…”
Section: Introductionmentioning
confidence: 99%
“…The immiscibility of cobalt in Pb (less than 0.02 wt.%) is accompanied by a microstructural heterogeneity of lead alloyed anodes. However, segregation and heterogeneous distribution of alloying elements during casting can lead to a significant decrease in the reliability and controllability of lead alloyed anodes in industrial performance [ 8 ]. Some techniques, such as pre-alloying Co with Sb, Sn, and Bi and then alloying with Pb; cementation of Co in liquid lead chloride salt; melting of Pb and Co followed by fast cooling; pulse electroplating; mechanical alloying; and spraying of Co on the surface of Pb sheets followed by rolling, have been examined by some researchers [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The vanadium ions do not get incorporated in the cobalt metal. Titanium or molybdenum can be used instead of vanadium (Lakshminarayanan et al, 1976). Matsumoto et al (1995) showed that anodic cobalt oxide deposition on platinum is suppressed when lanthanide ions are present in the electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Η ισοτροπία των ιδιοτήτων του σύνθετου υλικού, εξαρτάται άμεσα από το ποσοστό και την ομοιόμορφη διασπορά του ενισχυτικού υλικού στη μεταλλική μήτρα, μιας και το ενισχυτικό μέσο είναι αυτό που υφίσταται το μεγαλύτερο μέρος των φορτίσεων και αντιστέκεται στις καταπονήσεις που μεταφέρονται μέσω της μεταλλικής μήτρας. Επιπλέον, η ομοιόμορφη κατανομή των σωματιδίων καθυστερεί την εκτεταμένη μεταφορά των παραμορφώσεων στη μεταλλική μήτρα, με αποτέλεσμα το υλικό να είναι ανθεκτικότερο στις πλαστικές παραμορφώσεις[133,134].Πρόσφατες ερευνητικές μελέτες απέδειξαν ότι η ενσωμάτωση στη μεταλλική μήτραNi μικροκαψουλών ελαίου, οι οποίες συναποτίθενται υπό καθεστώς συνεχούς αλλά και παλμικού ρεύματος, οδηγούν σε αποθέματα με βελτιωμένη αντιδιαβρωτική συμπεριφορά κατά την έκθεσή τους σε περιβάλλον αλατωνέφωσης[139].Η ικανότητα αυτολίπανσης των επιφανειών αυτών συνίσταται στο γεγονός ότι κατά την επιβολή δυνάμεων τριβής τα επιφανειακά στρώματα του στερεού λιπαντικού, αποδεσμεύονται από το σώμα της μήτρας και καλύπτουν την επιφάνεια, μειώνοντας με τον τρόπο αυτό τον συντελεστή τριβής. Η διαδικασία αυτή συνεχίζεται και τα σωματίδια που βρίσκονται μέσα στη μεταλλική μήτρα αποδεσμεύονται σταδιακά, καθώς η μήτρα φθείρεται, με αποτέλεσμα να μειώνεται ο συντελεστής τριβής και η απώλεια υλικού λόγω φθοράς[128].Συστήματα που λειτουργούν σύμφωνα με αυτή την διαδικασία και χρησιμοποιούνται ευρύτατα στη βιομηχανία είναι το σύστημα, Cu/SiC που χρησιμοποιείται ως επικάλυψη σε ηλεκτρικές επαφές, και Ni/SiC, CoNi/Cr 3 C 2 που χρησιμοποιούνται σε επικαλύψεις ρουλεμάν και μηχανικών μερών αυτοκινήτων και αεροπλάνων[141,142].Εκτός από τις στερεές λιπαντικές ουσίες, πρόσφατα αναπτύχθηκε μια νέα τεχνική ενσωμάτωσης στη μεταλλική μήτρα πολυμερικών μικροκαψουλών που περιέχουν υγρό (νερό ή λάδι)[143].…”
unclassified
“…Η γήρανση επηρεάζει ορισμένα συστήματα μετάλλουσωματιδίων. Έτσι διαπιστώθηκε μείωση του ποσοστού ενσωμάτωσης της γ-Al 2 O 3 σε μήτρα Cu με την γήρανση του λουτρού, ενώ αντίθετα το ποσοστό της γ-Al 2 O 3 σε μήτρα Cr δεν μεταβλήθηκε με τη γήρανση του λουτρού[134,145]. Η γήρανση των ηλεκτρολυτικών λουτρών ελέγχεται με διάφορες πειραματικές μετρήσεις και όπου κρίνεται αναγκαίο γίνεται αναγέννηση τους.Σημαντικό ρόλο στη δημιουργία συνθηκών πραγματοποίησης ή μη μια ηλεκτρολυτικής συναπόθεσης, παίζει η παρουσία προσθέτων στο ηλεκτρολυτικό λουτρό.…”
unclassified